Ceramics for dental restorations – an introduction (2010)
Dental ceramics are the preferred materials for oral restoration due to some characteristics, such as adequate esthetics, high fracture strength and chemical stability. Currently, dental professionals have a large amount of ceramic systems to choose from, all of them having small differences regarding their chemistry, processing temperatures, mechanical strength and clinical applications. These differences lead to classification systems that are difficult to understand by professionals outside the dental field. The aim of this work is to review the current dental ceramic systems and present them from a compositional perspective to assure the comprehension of these materials by professionals who belong to the Biomedical Engineering field. A great effort was made to avoid classification methods imposed by manufacturers and to obtain a quick compilation of available information from the literature allowing the reader to have a general view of the state-of-the-art on dental ceramics.